Neovaginoplastia com pele de tilápia: avaliação citológica e bacterioscópica - Teófilo, Cristiana Rodrigues (2022)
Objective: To evaluate the cytology and vaginal microbiota findings of patients with Mayer-Rokitansky-Kuster-Hauser syndrome undergoing neovaginoplasty surgery using Nile tilapia skin. Methods: Descriptive cross-sectional study in which vaginal content was collected from women with Mayer-Rokitansky-Kuster-Hauser syndrome undergoing neovaginoplasty with Nile tiapia skin. Conventional oncotic cytology, hormonal cytology and Gram bacterioscopy were performed, in addition to colposcopy, between 12 and 24 months after performing the new surgical technique, between 2019 and 2021. The Nugent score was calculated. Data were categorized in Microsoft Excel for descriptive statistical analysis of the variables studied. The project was approved by the Ethics and Research Committee of the institution. Results: Squamous cells without atypia were found in the 7 patients. Five patients had an intermediate vaginal microbiota, with a Nugent score of 4, determined by the presence of few lactobacilli on Gram stain. In the evaluation of hormonal cytology, four patients presented a classification compatible with menacme. No colposcopic changes were observed. Total vaginal length remained greater than 6 centimeters after 12 months of follow-up when correct post-surgical dilatation was performed. Conclusions: There was the presence of squamous cells without atypia in the neovaginas with Nile tilapia skin. Most of the vaginal contents showed intermediate microbiota, with hormonal results compatible with menacme. Studies with a greater number of patients are necessary for a more comprehensive knowledge about the microbiome in the neovagina with NTFS, thus enabling support for the treatment and prevention of associated pathologies